QTL Mapping for Agronomic and Adaptive Traits Confirmed Pleiotropic Effect of mog Gene in Black Gram [Vigna mungo (L.) Hepper] - Somta, Prakit; Chen, Jingbin; Yimram, Tarika; Yundaeng, Chutintorn; Yuan, Xingxing; Tomooka, Norihiko; Chen, Xin (Frontiers in Genetics, 2020)
The results showed that most of the traits (100-seed weight, leaf size, and plant height) showed moderate narrow-sense heritability (h2) (45% to 65%), while pod size and seed length showed high h2 (>75%) and pod dehiscence (shattering), seed width and days to flowering showed low h2 (<35%). The QTLs for the traits was mapped onto a high-density linkage map developed for the RIL population.Inclusive composite interval mapping identified in total 42 QTLs for the 16 traits with number of QTLs per trait ranging from one to six. QTLs for the MOG phenotypes were mapped to linkage group 6, confirming the pleiotropic effect of the mog gene. Effect of the mog gene/QTL for the mog phenotypic variations was not high, ranging from about 15% in plant height to 40% in leaf area, leaf width and pod width. For 100-seed weight which is the most interesting trait, the mog gene/QTL contributed about 30% of the total trait variation 3 and showed additive effect of only 0.51 g which is only about 1.5-fold higher than of the other five QTLs detected for this trait. These results indicated that expression of mog gene is highly affected by environment and effect of the gene towards organ size and plant height is not extraordinary high. Implications of the findings of this study and exploiting of the MOG mutant in breeding were discussed.